Citizenship under fire : democratic education in times of conflict - Ben-Porath, Sigal R., 1967- (Princeton University Press, 2006)
Citizenship under Fire examines the relationship among civic education, the culture of war, and the quest for peace. Drawing on examples from Israel and the United States, Sigal Ben-Porath seeks to understand how ideas about citizenship change when a country is at war, and what educators can do to prevent some of the most harmful of these changes. Perhaps the most worrisome one, Ben-Porath contends, is a growing emphasis in schools and elsewhere on social conformity, on tendentious teaching of history, and on drawing stark distinctions between them and us. As she writes, "The varying characteri